Supercritical fluid extraction of bioactive compounds from Lycium chinense and Lycium barbarum - Aihemaiti, Zulipiye (Kulliyyah of Engineering,International Islamic University Malaysia, 2017)
Cancer is one of the most dangerous diseases, and breast cancer contributes to 22.9 percent of all cancers excluding non-melanoma skin cancer. There are several plant extracts which were reported for their potential to be used in cancer treatment. This includes L. chinense and L. barbarum which have been reported to contain abundant bioactive compounds with a lot of medicinal properties such as anti-cancer and powerful anti-oxidant. One of the advanced technologies that can be used to extract these bioactive compound is supercritical fluid extraction (SFE), replacing the conventional extraction methods that have several disadvantages. However, no report is available on supercritical fluid extraction for L. chinense and L. barbarum fruits. Therefore, in this study, supercritical fluid extraction was used to extract bioactive compounds from L. chinense and L. barbarum fruit. Optimization of the extraction yield were conducted using Response Surface Methodology for three important parameters namely temperature, co-solvent and time. Under different extraction conditions 15 experiments were designed and studied. The optimum yields from L. chinense and L. barbarum were 0.0656g/g and 0.0332g/g, respectively, which was attained within 60 minutes extraction times at 45 °C using 20% co-solvent. Co-solvent and extraction time had the most significant effect on the yield (p<0.05) while temperature showed minor influence on the yield of crude extraction. Furthermore, the assay for bioactive compound such as antioxidant and cytotoxicty were also cunducted for both L. chinense and L. barbarum crude extract. Anti-oxidant activity of 20mg/ml of L. chinense crude extract shows higher DPPH free radical scavenging capacity with 82.79% compared to 20mg/ml of L. barbarum crude extract with 81.75% of DPPH scavenging capacity. However, 20mg/ml of L. chinense and L. barbarum crude extracts on DPPH free radical scavenging were higher to that of 0.1mg/ml of BHA (81.71%) and 0.115mg/ml of BHT (73.87%). In addition, 20mg/ml of L. barbarum crude extract on ABTS+ radical indicated higher anti-oxidant capacity with 93.95% compared to 20mg/ml of L. chinense crude extract with 87.93% of scavenging capacity. However, the results for 20mg/ml of L. chinense crude extract ABTS+ free radical scavenging was lower to 0.2mg/ml of BHA (93.90 %) and 0.4mg/ml of Vitamin C (93.61%). On the other hand, the 20mg/ml of L. barbarum crude extract on ABTS+ free radical scavenging showed higher anti-oxidant than 0.2mg/ml of BHA and 0.4mg/ml of Vitamin C with 93.90% and 93.61%, respectively. Furthermore, L. chinense crude extract shows higher cytotoxic activity with IC50 value of 1126.4530µg/ml compared to L. barbarum crude with IC50 value of 1919.304µg/ml. However, when compared to Taxol, L. chinense crude extracts showed much lower cytotoxic activity as Taxol's IC50 value was 0.122µg/ml. This result was expected as the L. chinense and L. barbarum crude extract were not purified while Taxol used was highly purified. However, the cytotoxic activity in L. chinense and L. barbarum crude extract indicated their potential as cytotoxic agent.